2009
DOI: 10.1111/j.1466-8238.2009.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the onset of spring growth in shrubland species in response to experimental warming along a north–south gradient in Europe

Abstract: Aim To test whether the onset of spring growth in European shrublands is advanced in response to the warmer conditions projected for the next two decades by climate models, and, if there is a change, whether it differs across Europe. LocationThe studied sites spanned a broad north-south European gradient with average annual temperatures (8.2-15.6 ° C) and precipitation (511-1427 mm).Methods 'Bud break' was monitored in eight shrub and grass species in six European sites under control and experimentally warmer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 64 publications
5
31
0
2
Order By: Relevance
“…These results suggest that warmer periods in spring under predicted climate change will enhance the capacity of this species to convert light energy to fixed carbon. Springtime temperature limitation for P. alba is in line with the South Eurasian affinity of this species, and is supported by earlier budbreak in spring in warmed plots relative to control in the same experiment (Prieto et al 2009b). Consistent with our results, the negative impact of low temperature (or the positive influence of warming treatment) on photochemical performance (Fv/Fm) was reported for other thermophilous Insert Table 4 here.…”
Section: Responses To Temperaturesupporting
confidence: 80%
“…These results suggest that warmer periods in spring under predicted climate change will enhance the capacity of this species to convert light energy to fixed carbon. Springtime temperature limitation for P. alba is in line with the South Eurasian affinity of this species, and is supported by earlier budbreak in spring in warmed plots relative to control in the same experiment (Prieto et al 2009b). Consistent with our results, the negative impact of low temperature (or the positive influence of warming treatment) on photochemical performance (Fv/Fm) was reported for other thermophilous Insert Table 4 here.…”
Section: Responses To Temperaturesupporting
confidence: 80%
“…g S and Yield at midday were also lower in the warming treatment than under control conditions (p ≤ 0.01; Figures 4b and 5b). It has been reported that drought and warming can advance the spring growing season, affect reproductive performance and decrease plant productivity of E. multiflora [63,64]. The drier and warmer conditions projected for the future could affect diversity, decrease biomass and increase mortality in Mediterranean ecosystems [11,18,21,65].…”
Section: Pri Assessment Of Seasonal Photosynthesis Under Long-term Drmentioning
confidence: 99%
“…fine root biomass increased by warming, perhaps due to increased root number by warming during spring (Edwards et al 2004). Prieto et al (2009b) also found that the acceleration of spring growth was the most common response to warming and Soolanayakanahally et al (2013) proved that spring flush was primarily temperature driven, especially in boreal trees.…”
Section: Warming Effect On Roots Varied With Growth Periodmentioning
confidence: 85%